Computer-assisted assessment in teletandem interactions - CONSOLO , Douglas Altamiro (The ESPecialist, 2022)
Assessment constitutes an essential dimension of learning and in teletandem interactions inasmuch as it helps interactants to verify indications of language development and the achievement of learning goals. In this paper I review computer-aided assessment (CAA) in foreign language learning with a focus on data from a partnership in the Teletandem Brazil Project: foreign languages for all. I draw on the literature on language assessment and CAA, the latter defined as any type of activity in which computers are used to support assessment beyond their functions to store and transmit information. Then I discuss excerpts from a teletandem session, considering occasions in which teletandem interactants evaluate each other’s linguistic performances. Assessment in that session is mainly characterized by different types of feedback provided by the most proficient interactant. The less proficient interactant is given feedback based on principles that underpin conversation, distance learning and teletandem, such as the use of technological resources and negotiation about how and when assessment should occur. These principles do not characterise a new paradigm in language assessment, since the conversational and linguistic criteria on which evaluation is based are similar to criteria for assessment in other contexts, for example, in face-to-face lessons.